Functional analysis of humor verbal behavior (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Based on Skinner’s Verbal Behavior (Skinner, 1957), this study intended a functional analysis of verbal humor in four parodies from the poem “Canção do Exílio” by Gonçalves Dias (1846). We identified the stimulus control for the author’s responses and the consequences that may have controlled the behavior of the authors.The formal and thematic sources of each work and the causes of humorous effect intended by the authors of the parodies were identifies through functional analysis of the verbal responses. It was found that the context and timing are paramount to generate humorous effect. The controlling variables (sources) supplement the context specifically, generating the humorous effect. It was concluded that the analysis is subject to extension to non-verbal field, and that laugh is a consequence for the author’s humurous response and not the behavior.
Keywords: Humor; Parody; Verbal Behavior; Functional Analysis of Behavior